Diagnostic value of semen analysis in male infertility - Agrawal, Sakshi; Gadre, A. S.; Dravid, N. V.; Agrawal, Sumedh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Aim was to analyze semen parameters according to WHO criteria (5th edition) in patients attending infertility OPD and compare it with 6th edition. Methods: It was a retrospective descriptive cross sectional study that took place at the department of pathology, JMF ACPM medical college, Dhule, Maharashtra. This study included 103 subjects who were presented for semen analysis from June 2022 to June 2024. The data regarding ejaculate volume, count, motility and morphology were collected. Results: Abnormal semen quality was a major factor of infertility in our rural setup with 39% of male partners of infertile couples having abnormal semen parameters. Conclusions: Male contribution towards infertility is yet to be studied and requires more elaborate research.